Predicting Burnout Among Juvenile Detention and Juvenile Probation Officers - Rhineberger-Dunn, Gayle (Criminal justice policy review, 2020)
The purpose of our study is to extend the existing literature by assessing the predictors of burnout among juvenile justice staff. We assess the impact of individual, job/role-related, and organizational factors on burnout among juvenile probation and juvenile detention officers. Also, given recent research in the institutional and community corrections field, we evaluate which set of variables (e.g., individual, job/role related, and organizational) has a greater impact on burnout. Results indicate that the only individual-level variable affecting burnout is contact hours, and only for emotional exhaustion. Role overload is also significant only for emotional exhaustion, whereas work-family conflict is significant for both emotional exhaustion and depersonalization. Furthermore, input into decision making and lack of opportunities are both significant for depersonalization and personal accomplishment. Finally, job characteristics appear to have a greater impact than organizational variables on both emotional exhaustion and depersonalization, but organizational variables have a stronger influence on personal accomplishment.